"Pseudotumors" in dermatology - Vishal Gaurav; Chander Grover (Wolters Kluwer Medknow Publications, 2022)
In dermatology, "pseudo" is often used as a prefix for entities resembling another standard condition, either morphologically or histopathologically. Correspondingly, "pseudotumor" is a term encompassing dermatological conditions which are not true proliferations, but either have a clinical resemblance to a known tumor (e.g., Pseudokaposi's sarcoma is actually a non-neoplastic condition) or a histopathological resemblance to one (e.g., pseudo-myogenic hemangioendothelioma named due to a histopathological resemblance between myocytes and tumor cells). Often such a nomenclature can create confusion and unnecessary alarm for both the physicians and the patients. Through this article we attempt to summarise "pseudotumors" in dermatology and classify them into clinical and histopathological "pseudotumors", so as to produce a ready reckoner for this confusing nomenclature.